O-016 Development and Validation of an Endovascular Chemotherapy Filter Device for Removing High-Dose Doxorubicin from the Blood: In Vivo Porcine Study. (26th July 2014) - Patel, A; Chin, A; Yang, J; Thorne, B; Saeed, M; Wilson, M; Hetts, S
Abstract : Purpose: A novel disposable endovascular chemotherapy filter (CF) device was developed to remove excess doxorubicin (Dox) from the blood during intra-arterial chemotherapy delivery to prevent systemic toxicities. Previous proof-of-concept established the capacity of the filter to bind Dox in swine serum in vitro. In this study, CF navigation, deployment and in vivo Dox binding was evaluated in the porcine inferior vena cava (IVC). Materials and methods: An 18 Fr CF device was constructed with an ion-exchange membrane attached to an expandable 28 mm diameter Nitinol frame. Under X-ray fluoroscopy and contrast venography, the CF was percutaneously introduced via the internal jugular vein and deployed in the porcine infrarenal IVC. 50 mg of Dox (2 mg/ml) was injected over 10 min in the IVC below the CF device. Venous catheters with tips proximal and distal to the CF device in the infrarenal IVC obtained pressures and blood samples for Dox concentrations over 90 min across the CF device membrane. Results: The CF device was successfully introduced and deployed in the infrarenal IVC in vivo. Visualization under X-ray fluoroscopy verified the proper placement and mechanical expansion of the Nitinol framework. In a 90 min study, the device was biocompatible, not leading to hemodynamic disturbances: pressure measurements taken throughout the experiment yielded a max gradient of 17 mmHg across the CF membrane. Venography demonstrated non-flow-limiting thrombus associated with the CF device after 90 min of deployment (swine were not heparinized). Significant Dox binding was noted with an 85%, 74%, and 83% decrease in relative pre- versus post-filter Dox concentrations at times 3, 10, and 30 min, respectively after Dox injection. Conclusion: We developed a biocompatible CF device that can be safely introduced, deployed, and removed from the IVC in vivo. The CF device demonstrated significant Dox binding, and could serve as a platform technology in drug therapy to allow for higher regional doses of drug while limiting systemic toxicity. In future in vivo experiments, animals or the CF device itself may be heparinized in order to prevent thrombosis. When fully developed, indications for this device could include head and neck cancer, with the device deployed in the superior vena cava or internal jugular veins during selective IA chemotherapy. Disclosures: A. Patel: 1; C; NIH-NCI. 4; C; ChemoFilter. A. Chin: 1; C; NIH-NCI. 4; C; ChemoFilter. J. Yang: None. B. Thorne: None. M. Saeed: None. M. Wilson: 1; C; NIH-NIBIB, NIH-NCI. 4; C; ChemoFilter. S. Hetts: 1; C; NIH-NIBIB, NIH-NCI, Siemens, Covidien. 2; C; Stryker, Penumbra, Silk Road Medical, Medina Medical. 4; C; ChemoFilter, Medina Medical, DriftCoast.